Tropical orchids in the North, Montréal Botanical Garden, Québec, Canada - Gobeille, Lise (Universidad de Costa Rica, 2015)
The Montréal Botanical Garden was founded, in 1931, by the remarkable botanist and scientist, catholic brother Marie Victorin. Since its foundation the garden has three missions : conservation, educa- tion and research. Certainly 76 years old is still young for a botanical garden, but it has accomplished a maturity and dynamism that is admired by many. The tropical collections are presented to the public by family and theme in ten public greenhouses. Behind the scene, more than 40 greenhouses serve for conser- vation of our collections, for production and for research. Situated on 75 hectares, 27 thematic gar- dens present the different collections while three gar- dens have a cultural vocation: the Chinese Garden, the Japanese Garden and the American Indian Garden. A total of 22,000 taxons are presented in our collections.